Enhanced Antioxidant Activity in Streptococcus thermophilus by High-Level Expression of Superoxide Dismutase - Kong, Linghui; Xiong, Zhiqiang; Song, Xin; Xia, Yongjun; Zhang, Hui; Yang, Ying; Ai, Lianzhong (Frontiers in Microbiology, 2020)
Superoxide dismutase (SOD) plays an essential role in eliminating oxidative damage of lactic acid bacteria. Streptococcus thermophilus, an important probiotic lactic acid bacterium, often inevitably suffers from various oxidative stress during dairy fermentation. In this study, to confer high-level oxidative resistance on S. thermophilus, the sod gene from Lactobacillus casei was heterologous expressed in S. thermophilus S-3 using our previous constructed native constitutive promoter library. The enzyme activity of SOD was significantly enhanced in S. thermophilus recombinant by overexpression of promoter #14 (2070 U). Furthermore, the strategy of multi-copy sod-expressing cassettes was employed to improve SOD activity. The maximum activity (2750 U) was obtained by the two-copy sod recombinant, which was 50% higher than that of one-copy recombinant. In addition, the survival rate of multi-copy sod recombinants was increased about 97-fold with 3.5 mmol/L H2O2 treatment. To our knowledge, this is the first report of multi-copy sod gene expression in S. thermophilus, which exerts a positive effect on coping with oxidative stress to enhance the potential of industrial application.